Mimicking Enzymatic Active Sites on Surfaces for Energy Conversion Chemistry - Gutzler, Rico (2015)
Metal-organic supramolecular chemistry on surfaces has matured to a point where its underlying growth mechanisms are well understood and structures of defined coordination environments of metal atoms can be synthesized in a controlled and reproducible procedure. With surface-confined molecular self-assembly, scientists have a tool box at hand which can be used to prepare structures with desired properties, as for example a defined oxidation number and spin state of the transition metal atoms within the organic matrix. From a structural point of view, these coordination sites in the supramolecular structure resemble the catalytically active sites of metallo-enzymes, both characterized by metal centers coordinated to organic ligands. Several chemical reactions take place at these embedded metal ions in enzymes and the question arises whether these reactions also take place using metal-organic networks as catalysts.Mimicking the active site of metal atoms and organic ligands of enzymes in artificial systems is the key to understanding the selectivity and efficiency of enzymatic reactions. Their catalytic activity depends on various parameters including the charge and spin configuration in the metal ion, but also on the organic environment, which can stabilize intermediate reaction products, inhibits catalytic deactivation, and serves mostly as a transport channel for the reactants and products and therefore ensures the selectivity of the enzyme. Charge and spin on the transition metal in enzymes depend on the one hand on the specific metal element, and on the other hand on its organic coordination environment. These two parameters can carefully be adjusted in surface confined metal-organic networks, which can be synthesized by virtue of combinatorial mixing of building synthons. Different organic ligands with varying functional groups can be combined with several transition metals and spontaneously assemble into ordered networks. The catalytically active metal centers are adequately separated by the linking molecules and constitute promising candiates for heterogeneous catalysts.Recent advances in synthesis, characterization, and catalytic performance of metal?organic networks are highlighted in this Account. Experimental results like structure determination of the networks, charge and spin distribution in the metal centers, and catalytic mechanisms for electrochemical reactions are presented. In particular, we describe the activity of two networks for the oxygen reduction reaction in a combined scanning tunneling microscopy and electrochemical study. The similarities and differences of the networks compared to metallo-enzymes will be discussed, such as the metal surface that operates as a geometric template and concomitantly functions as an electron reservoir, and how this leads to a new class of bioinspired catalysts. The possibility to create functional two-dimensional coordination complexes at surfaces taking inspiration from nature opens up a new route for the design of potent nanocatalyst materials for energy conversion.